2011
DOI: 10.1037/a0022437
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive–linguistic foundations of early spelling development in bilinguals.

Abstract: Developing spelling skills in English is a particularly demanding task for Chinese speakers because, unlike many other bilinguals leaming English as a second language, they must leam two languages with different orthography as well as phonology. To disentangle socioeconomic and pedagogical factors from the underlying cognitive-linguistic processes that predict the development of spelling, we used a 6-month longitudinal design and compared children with English as their first language (English-Ll; n = 50) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 103 publications
(177 reference statements)
2
19
1
2
Order By: Relevance
“…Despite their poorer phonological skills, these young bilingual children continued to rely on such skills for reading and spelling English. These findings are similar to studies conducted with Chinese-Ll children where the strongest predictor of English word reading and word spelling approximations was phonological awareness (Gottardo et al, 2001;McBride-Chang & Kail, 2002;Yeong & Rickard Liow, 2011). Furthermore, our findings showed that the same relationship between phonological skills and reading was evident for the older bilingual children.…”
Section: Discussionsupporting
confidence: 91%
“…Despite their poorer phonological skills, these young bilingual children continued to rely on such skills for reading and spelling English. These findings are similar to studies conducted with Chinese-Ll children where the strongest predictor of English word reading and word spelling approximations was phonological awareness (Gottardo et al, 2001;McBride-Chang & Kail, 2002;Yeong & Rickard Liow, 2011). Furthermore, our findings showed that the same relationship between phonological skills and reading was evident for the older bilingual children.…”
Section: Discussionsupporting
confidence: 91%
“…More recently, Sze and Rickard Liow (2011) also provided empirical evidence that L1 morphophonemic knowledge (i. e., the interaction of phonological and morphological components) generalizes from the dominant language during second language acquisition. However, the positive influence of one language on the acquisition of skills in the other language will be more limited when the phonological and morphological components of the children's two languages are as different as Mandarin and English (Chen et al, 2010;Rickard Liow & Lau, 2006;Yeong & Rickard Liow, 2011) or Cantonese and English (Wang & Geva, 2003).…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…This clear relationship between phonological awareness and literacy acquisition has been demonstrated both in monolingual English-speaking children and in bilingual children learning English as a second language (ESL) (McBride-Chang & Kail, 2002;McBride-Chang et al, 2008;Yeong & Rickard Liow, 2011). Despite this important connection to reading and spelling, the early development of phonological awareness itself has received relatively little attention in children learning to speak two languages with different phonological structures.…”
Section: Introductionmentioning
confidence: 99%
“…As is generally known, word writing (or spelling), like reading, involves vocabulary knowledge and temporary memory processes, as well as metalinguistic knowledge. Although the correlations for individual performance on single-word reading and spelling tasks are high (Pearson's r=0.89 for 157 children, Gedutienė 2008), children with language impairments and those at risk for dyslexia often find spelling more problematic than reading (Yeong & Liow 2011). It seems that spelling is the more challenging task, because unlike reading it requires fully specified orthographic lexical representations (Angelelli et al 2010).…”
Section: Discussionmentioning
confidence: 99%